G296(P) Implementation of a neonatal minimal dataset in a low income country. (12th March 2018) - Battersby, C; Loidl, V; Lloyd-Jones, R; Toussaint, P; Hill, C; Vasu, V
Abstract : Aim: To embed a neonatal minimal dataset into routine neonatal care in a low income country (LIC) to inform and promote quality improvement (QI). Method: In May 2016, we implemented the collection of a subset of data items held on the National Neonatal Research Database (UK) into a NGO funded neonatal unit in Haiti. Data were recorded at admission, discharge, and daily using standardised forms. Data were analysed for a six month period (1 st May to 31 st October 2016) to determine data completeness and provide feedback to staff for QI. Results: Data completeness was high for gestational age (GA) (98%), mode of delivery (100%), origin of admission (100%), outcome at discharge (94%) but lower for feeding at discharge (61%), temperature within an hour of admission (75%) and cause of death (73%). 301 babies were admitted in the six month period (72% term ≥37 weeks; 11% 34 to <37 weeks; 12% 30 to <34 weeks; 3% 28 to <30 weeks). 58% were born by vaginal delivery and 41% caesarean section (24% emergency, 17% elective). 73% were inborn, 23% from the community and 3% from another hospital. 58% were hypothermic (temp <36.5°C) and 5% had a temperature of <34°C. Overall mortality rate was 9%; by GA 28 to <30 weeks (22%); 30 to <34 weeks (31%); 34 to <37 weeks (9%);≥37 weeks (4%). Among babies born 30 to <34 w, the commonest cause of death was gastrointestinal haemorrhage. Among term babies, the most common cause of death was unknown or hypoxia. 34 babies received CPAP for a median 4 days (interquartile range 2–5). 79% received some breast milk during admission and 47% were exclusively breast fed at discharge. Conclusion: Our preliminary data have informed QI programmes aimed to reduce hypothermia on admission and mortality rates. We have shown that although it is feasible to collect a minimal dataset in a LIC setting, completeness of data can be a challenge, and we recommend regular feedback to neonatal staff to reinforce the importance of complete and accurate data to drive improvements in clinical care and outcomes.